Increased Peripheral NKG2A-NKG2D+CD3-CD16+CD56dim NK Cell Subset Was Positively Correlated with Antiphospholipid Antibodies in Patients of Obstetric Antiphospholipid Syndrome. (17th February 2022) - Zhang, Yinmei; Zhao, Yang; Si, Wenzhe; Yang, Boxin; Lin, Mingmei; Zheng, Jiajia; Cui, Liyan
ABSTRACT: Obstetric antiphospholipid syndrome (OAPS) is an autoimmune disorder with severe life-threatening complications shown during pregnancy. It has been reported that the increase in CD16 + CD56 dim natural killer (NK) cells in peripheral blood are risk factors for recurrent miscarriages, but this expression of CD16 + CD56 dim NK cells in OAPS patients has not been reported, and the mechanism is not clearly illustrated. In this study, we compared the distributional profiles of different NK cell subsets and the expressions of NK cell-activating receptors in peripheral blood of patients with OAPS and healthy women. Our results showed significantly increased NKG2A − NKG2D + subset and decreased NKG2A + NKG2D − subset in CD3 − CD16 + CD56 dim NK cells, CD3 − CD16 − CD56 bright NK cells and CD56 + T cells in OAPS patients compared with those in healthy control women. The CD27 − CD11b + subset significantly increased in CD3 − CD16 + CD56 dim NK cells in OAPS patients compared with those in healthy control women. In addition, the NKG2A − NKG2D + subset in CD3 − CD16 + CD56 dim NK subset in triple positivity was higher than single positivity OAPS patients. At the optimal diagnostic threshold established by ROC analysis, using the cut-off of NKG2A − NKG2D + and CD27 − CD11b + subset in CD3 − CD16 + CD56 dim NK cells is 10.10% and 92.75%, the sensitivity of NKG2A − NKG2D + and CD27 − CD11b + to detect patients with OAPS compared with healthy control results was 94.1% and 60.8%, and specificity was 84.2% and 89.5%, respectively, with an area under the curve (AUC) of 0.903 and 0.829, respectively. The NKG2A − NKG2D + subset in CD3 − CD16 + CD56 dim NK cells was positively correlated with the antiphospholipid antibodies lg anti-aCL IgG, lg anti-aCL IgM, lg anti-aCL IgA, lg anti-β2GP1 IgM and Complement 4(C4), while the CD27 + CD11b + subset in CD3 − CD16 + CD56 dim NK cells was correlated with lg anti-β2GP1 IgG and lg anti-β2GP1 IgA. These results suggested that the NK cytotoxic function enhanced in OAPS patients and unbalanced of NK activating receptors and inhibiting receptors may contribute to the immune pathogenesis of OAPS.